Transformative Learning: A Precursor to Preparing Health Science Students to Work in Indigenous Health Settings?. Issue 2 (December 2019) - Bullen, Jonathan; Roberts, Lynne
Abstract : Australian undergraduate programmes are implementing curriculum aimed at better preparing graduates to work in Indigenous health settings, but the efficacy of these programmes is largely unknown. To begin to address this, we obtained baseline data upon entry to tertiary education (Time 1) and follow-up data upon completion of an Indigenous studies health unit (Time 2) on student attitudes, preparedness to work in Indigenous health contexts and transformative experiences within the unit. The research involved 336 health science first-year students (273 females, 63 males) who completed anonymous in-class paper questionnaires at both time points. Paired sample t -tests indicated significant change in student attitudes towards Indigenous Australians, perceptions of Indigenous health as a social priority, perceptions of the adequacy of health services for Indigenous Australians and preparedness to work in Indigenous health settings. Hierarchical multiple regression analyses indicated that after controlling for Time 1 measures, the number of precursor steps to transformative learning experienced by students accounted for significant variance in measures of attitudes and preparedness to work in Indigenous health contexts at Time 2. The knowledge gained further informs our understanding of both the transformative impact of such curriculum, and the nature of this transformation in the Indigenous studies health context.